Durio tanjungpurensis (Malvaceae), a new species and its one new variety from west Kalimantan, Indonesia - Navia, Zindi Ilman; Chikmawati, Tatik (Bangladesh Journal of Botany, 2018)
A new species and a new variety of Durio Adanson from West Kalimantan are described namely, Durio tanjungpurensis Z.I. Navia, sp. nov. and D. tanjungpurensis var. tembaganensis Navia, var. nov. The new species has small fruits (5 - 8 cm in diam), brown to yellowish green pericarp, milky white thin aril (<1 mm), and not edible. It is related to D. testudinarum Becc. Durio tanjungpurensis varies in its flower and fruit characters. The new variety differed from D. tanjungpurensis Z.I. Navia, sp. nov. in six characters, i.e. leaf ovate, petal oblanceolate with apex round, fruits on the branches, on the stem, at the base of trunk, no-spine area in fruit apex, pericarp green to yellowish green, aril only 20 - 40% covering the seeds.